Pelatihan Aplikasi E-Learning “MojadiPro” Berbasis Android untuk Siswa SMK IT Raflesia Depok - Agus Subekti; Zico Pratama Putra; Dwiza Riana; Hilman Ferdinandus Pardede (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
SMK IT Raflesia Depok is one of the high schools in the Depok City area which currently has a website that is used as a medium of information and communication, but does not yet provide teaching material services online. Apart from getting subject matter from school, students are usually still looking for additional material by attending private classes. With the development of technology that has developed in the field of education, access to subject matter can be done online, or what is commonly called e-learning. In order to carry out the Tri Dharma of Higher Education, Nusa Mandiri University held an android-based "MojadiPro" e-learning application training for students of SMK IT Raflesia Depok which aims to provide information regarding the existence of the MojadiPro e-learning application, which later can be used by students as a companion application learning that can be accessed via a smartphone. The training was held on January 14 2023 at UNM Margonda Campus with 15 participants. The research results can increase participants' understanding of the development of e-learning from time to time and the technology used in the development of e-learning platforms